Activated flux TIG welding of non- ferrous metals - (:unkn) unknown (NATL INST SCIENCE COMMUNICATION-NISCAIR, 2019)
TIG welding process has high levels of stability and permits more refined control than the majority of other arc welding processes. The principal disadvantages of TIG lie in the limited thickness of material which can be welded in a single pass. Activated Flux Tungsten Inert Gas (A-TIG) welding can increase the joint penetration and weld depth/width ratio, thereby reducing angular distortion of the weldment. In this review paper, A-TIG welding properties of nonferrous metals are examined. How the flux increases the penetration depth is explained and then the effects of the chemical composition and thickness of the flux are described in detail.
Keywords: TIG welding; A-TIG welding; Non-ferrous metals welding; CADMIUM CHLORIDE FLUX; MECHANICAL-PROPERTIES; OXIDE FLUXES; MAGNESIUM; MICROSTRUCTURES; PENETRATION; TITANIUM; ALLOYS